2017
DOI: 10.1038/npp.2017.226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intranasal Oxytocin on the Blood Oxygenation Level-Dependent Signal in Food Motivation and Cognitive Control Pathways in Overweight and Obese Men

Abstract: Recent research indicates that the hypothalamic neuropeptide hormone oxytocin is a key central nervous system factor in the regulation of food intake and weight. However, the mechanisms underlying the anorexigenic effects of oxytocin in humans are unknown and critical to study to consider oxytocin as a neurohormonal weight loss treatment. We performed a randomized, double-blind, placebo-controlled crossover study with single-dose intranasal oxytocin (24 IU) in ten overweight or obese, otherwise healthy men. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 48 publications
5
42
0
Order By: Relevance
“…The anorexigenic properties of OXT appear to be mediated by homeostatic and reward‐related neural pathways . Studies in humans support these mechanisms, and also indicate that OXT may act via modulating impulse control circuitry . Although studies in animal models show that acute or chronic administration of OXT increases energy expenditure, single dose i.n.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The anorexigenic properties of OXT appear to be mediated by homeostatic and reward‐related neural pathways . Studies in humans support these mechanisms, and also indicate that OXT may act via modulating impulse control circuitry . Although studies in animal models show that acute or chronic administration of OXT increases energy expenditure, single dose i.n.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly OXT reduces food intake in fasted and fed states with preferential effects in reducing sweet, fatty and salty foods, suggesting effects on both homeostatic and hedonic eating. Mechanistic studies using functional magnetic resonance imaging (fMRI) have confirmed that OXT modulates homeostatic (eg, hypothalamus) and hedonic (eg, ventral tegmental area, orbitofrontal cortex, insula) neurocircuitry in response to food images. In addition, fMRI studies have shown that OXT increases activation of brain regions responsible for self‐control (eg, anterior cingulate cortex, prefrontal cortex, supplementary motor area) .…”
Section: Effects Of In Oxytocin Administration On Energy Homeostasis mentioning
confidence: 99%
See 1 more Smart Citation
“…Whole-brain analysis by functional magnetic resonance imaging also showed reduced activation in reward-related food motivation brain regions in subjects treated with oxytocin. In addition, oxytocin administration was associated with reduced activity in the hypothalamus, a region central to homeostatic control of feeding, in male subjects across the weight spectrum (118,119). Oxytocin also increased functional magnetic resonance imaging activation in brain regions involved in cognitive control, a process that enables individuals to suppress behavioural impulses to achieve a desired outcome, e.g.…”
Section: Oxytocin System In Energy Balancementioning
confidence: 99%
“…In fact, intranasal oxytocin treatment in human has been widely studied (Sippel et al, 2017), mainly in the context of eating disorders (Kim, Eom, Leppanen, Leslie, & Treasure, 2018;Kim, Kim, Cardi, et al, 2014;Kim, Kim, Park, Pyo, & Treasure, 2014;Leppanen et al, 2017). This intranasal treatment suppresses hypothalamic activation in response to visual food cues (van der Klaauw et al, 2017) and causes bilateral VTA hypoactivation to high-calorie food stimuli and also in additional hedonic pathways (Plessow et al, 2018). Furthermore, intranasal oxytocin appears to limit food intake in humans by enhancing the activity of fronto-cortical brain areas that establish cognitive control processes, thereby overriding the hedonic drive to eat (Spetter et al, 2018).…”
Section: Central Oxytocin and Food Rewardmentioning
confidence: 99%